1995
DOI: 10.1212/wnl.45.7.1268
|View full text |Cite
|
Sign up to set email alerts
|

Copolymer 1 reduces relapse rate and improves disability in relapsing‐remitting multiple sclerosis

Abstract: We studied copolymer 1 (Copaxone) in a multicenter (11-university) phase III trial of patients with relapsing-remitting multiple sclerosis (MS). Two hundred fifty-one patients were randomized to receive copolymer 1 (n = 125) or placebo (n = 126) at a dosage of 20 mg by daily subcutaneous injection for 2 years. The primary end point was a difference in the MS relapse rate. The final 2-year relapse rate was 1.19 +/- 0.13 for patients receiving copolymer 1 and 1.68 +/- 0.13 for those receiving placebo, a 29% redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
1,027
5
54

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,804 publications
(1,105 citation statements)
references
References 0 publications
19
1,027
5
54
Order By: Relevance
“…Patients experience flushing, chest tightness, dyspnea, palpitations, and anxiety. The duration is about 30 seconds to 30 minutes, resolving spontaneously [84]. In the initial phase three trial, IPISRs were observed in 19 participants (15.2 %) compared with 4 (3.2 %) of placebo.…”
Section: Clinical Usementioning
confidence: 99%
See 1 more Smart Citation
“…Patients experience flushing, chest tightness, dyspnea, palpitations, and anxiety. The duration is about 30 seconds to 30 minutes, resolving spontaneously [84]. In the initial phase three trial, IPISRs were observed in 19 participants (15.2 %) compared with 4 (3.2 %) of placebo.…”
Section: Clinical Usementioning
confidence: 99%
“…Beginning in October 1991, the Copolymer 1 Multiple Sclerosis Study group conducted a 2 year, double-blind, placebo-controlled trial with 251 participants who had an EDSS of 0-5 and a history of at least 2 relapses in the prior 2 years, including 1 in the last year [84]. Participants were well matched and withdrawals from each group were similar with 15 % withdrawing from the GA group and 13.5 % from placebo.…”
Section: Relapsing Remitting Msmentioning
confidence: 99%
“…Their long-term beneficial effects are uncertain and often detrimental side-effects have been reported (Johnson et al, 1995;Filippini et al, 2003). This review addresses the role of nutrition in MS. We discuss the potential of directly acting nonenzymatic antioxidants for dietary supplementation and elaborate on the role of longchain n-6 and n-3 PUFAs in immunosuppression, cellular function and remyelination.…”
Section: Treatment Strategies In Msmentioning
confidence: 99%
“…It was designed to simulate myelin basic protein, a putative target antigen in MS. After it was found to inhibit experimental autoimmune encephalomyelitis (EAE), a pilot study suggested that it had a beneficial effect in relapsing-remitting MS. 48 An extensive multi-centre, double-blind, placebocontrolled trial has now shown that the daily S.C. injection of 20 mg of copolymer 1 for 2 years significantly reduces the relapse rate of relapsing-remitting MS by 29% compared to placebo. 49 There was also some evidence that copolymer 1 had a beneficial effect on the progression of disability. The treatment was well tolerated.…”
Section: Copolymer 1 (Glatiramer Acetate)mentioning
confidence: 99%